2013
DOI: 10.1021/ac401966d
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Templated Silver Nanoclusters for Fluorescence Turn-on Assay of Acetylcholinesterase Activity

Abstract: We have developed a fluorescence turn-on assay using DNA-templated silver nanoclusters (Ag NCs) (i.e., 12 polycytosine-templated silver nanoclusters, dC12-Ag NCs), which is amenable to rapid, ultrasensitive assay of acetylcholinesterase (AChE). The detection mechanism is based on the concept, that is, AChE hydrolyzes the acetylthiocholine (ATCh) chloride to produce thiocholine (TCh). Subsequently, TCh sensitively and rapidly reacts with dC12-Ag NCs via Ag-S bond forming and enhances the fluorescence of dC12-Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(52 citation statements)
references
References 54 publications
2
50
0
Order By: Relevance
“…4E). This value is in the same order of magnitude as those previously reported by other AChE assays (Lei et al, 2015;Zhang et al, 2013). It is essentially demonstrated that our ensemble-based fluorescence assay could be used to screen the potential AChE inhibitors.…”
Section: Ache Inhibitor Assaysupporting
confidence: 87%
See 1 more Smart Citation
“…4E). This value is in the same order of magnitude as those previously reported by other AChE assays (Lei et al, 2015;Zhang et al, 2013). It is essentially demonstrated that our ensemble-based fluorescence assay could be used to screen the potential AChE inhibitors.…”
Section: Ache Inhibitor Assaysupporting
confidence: 87%
“…Among them, fluorescent materials-based assays have several advantages and attractive potentials owing to their intrinsic high sensitivity and real-time monitoring with fast response time. Indeed, along with traditional organic fluorophores (Liu et al, 2012;Maeda et al, 2005), several novel fluorescent nanomaterials such as semiconductor quantum dots (Saa et al, 2010) and DNA templated metal nanoclusters Zhang et al, 2013) have already been utilized to assess AChE activity and screen its inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…They attributed this increase to either new charge transfer enabled by the Ag-S bond or by the change of the local environment brought by the thiols [130]. This enhancement was utilized to detect the acetylcholinesterase activity, where a free thiol was generated via the enzymatic reaction [131].…”
Section: Reactive Quenchersmentioning
confidence: 99%
“…Several quantification techniques on AChE (Holas et al, 2012;Miao et al, 2010;Sabelle et al, 2002;Feng et al, 2007;Wang et al, 2009;Peng et al, 2009;Golub et al, 2013;Liao et al, 2013aLiao et al, , 2013bZhang et al, 2013;Garai-Ibabe et al, 2014) have been developed, each of which is suitable for different purposes and can be improved on user demand. The existing methods can solve problems in AChE activity determination.…”
Section: Introductionmentioning
confidence: 99%